Urban Expansion and Loss of Watershed of Eleyele Dam in Ibadan, Nigeria - Adejumo, Samson A; Osunwale, Solomon (CSID Journal of Infrastructure Development, 2024)
The study examined human activities contributing to the depletion of the Eleyele watershed. The activities have grown over time due to urban expansion through population growth and land and space requirements, resulting in rapid land use and land cover change. The study sourced both quantitative and qualitative data. A total of 247 pre-tested questionnaires were administered to randomly selected residents in the four communities (Eleyele, Ijokodo, Awotan, and Idi Osan) abutting the Eleyele watershed. In-depth interviews were conducted with the heads of Eleyele Waterworks, the Forestry Department, and the Oyo State Ministry of Agriculture and Natural Resources. We used Remote Sensing and Geographical Information Systems (GIS) to analyze the change in land use and landcover within the watershed from 1987 to 2019. Findings revealed that activities such as fuelwood harvesting, indiscriminate waste dumping, sand excavation, and housing construction, among others, accounted for the watershed encroachment and depletion. Temporal analysis of landcover change between 1987 and 2019 indicated that water bodies decreased from 1.6 km2 to 1.3 km2 in 2019, natural vegetation decreased from 24.8 km2 to 14.9 km2 in 2019, and built-up area increased from 8.9 km2 to 20.1 km2 as of 2019. There is an inverse relationship between urban expansion and the loss of vegetation cover within the watershed. Proposed strategies to secure the watershed and reservoir include the construction of perimeter fencing around the watershed, a public enlightenment campaign, and the reestablishment of protective vegetation in undeveloped areas within the watershed.